Improving Student Polite Character in Online Learning in the Covid-19 Pandemic Period - Mohammad Rindu Fajar Islamy; Kokom Siti Komariah; Elis Kurniani; Faiza Maila Yusfiana; Syifa Marwah (CV. Creative Tugu Pena, 2022)
This study aims to track and formulate the strategies of teachers in building students' ethical manners during the online learning process which tends to decrease or even disappear. Since the presence of the Covid-19 virus outbreak, the learning system has transitioned from offline to online as a measure to control the wider virus outbreak. However, this online learning model still has many obstacles that arise, one of which is the decline in the polite character of students during implementation. When the camera is off, students are not known whether they listen to the teacher's explanation or not, several cases show that students sometimes do not follow lectures interactively, even though they are joined in a zoom link. If this kind of habituation is not responded to immediately by education practitioners, it can be fatal for the students' character to shift towards a negative direction, especially the character of politeness. This research study was carried out using a qualitative approach, where data collection used interview, observation and documentation techniques for five high school teachers from three different schools. Data analysis uses Miles and Huberman's work tools: Display data, Reduction data, Drawing, and Conclusion. The results of the study show several important points: 1) Online learning has an impact on reducing children's character, 2) online learning challenges are difficult to monitor student involvement in learning, 3) strategies for improving polite character include providing clear rules, reward and punishment systems, habituation through teacher example. , learning contracts between teachers and students, consistent monitoring of student assignments, giving pre-tests 5 minutes before learning, providing materials related to manners and 4) character building requires integral cooperation from all parties, both teachers, parents, students , the community, and the school. Keywords: Direct Learning Model, Learning Outcome, Classroom Action Research